2021
DOI: 10.21203/rs.3.rs-956230/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tumor-B-Cell Interactions Promote Isotype Switching to an Immunosuppressive IgG4 Antibody Response Through Upregulation of IL-10 in Triple Negative Breast Cancers

Abstract: Background: Triple negative breast cancer (TNBC) is an aggressive breast cancer for which there is currently no targeted therapy. Tumor-infiltrating B-cells (TIB) have been observed in tumor tissues of TNBC patients, but their functional role is unclear. IgG4 is one of four antibody subclasses of IgG expressed and secreted by B cells. Unlike other IgG isotypes, IgG4 has an immunosuppressive function and is induced by Th2-type cytokines. In cancers such as melanoma, IgG4 has been linked with advanced disease an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
1
0
0
Order By: Relevance
“…Our observation was corroborated by repeating the measurements using the same IgG4-specific secondary antibody as well as by using the same clone from an alternative source (including differences in concentrations and storage buffers), which makes us confident that the results presented are valid. Moreover, we presented one of the most comprehensive cross-validations to date of all secondary antibodies -widely used in research on SARS-CoV-2 (Crowley et al, 2021;Fraley et al, 2021;Kim et al, 2021;Lee et al, 2021;Newell et al, 2021;Phelan et al, 2021;Pullen et al, 2021;Yates et al, 2021) and in other fields (Minassian et al, 2021;Sanchez Vargas et al, 2021;Tschismarov et al, 2021;Jennewein et al, 2022;Toney et al, 2022) -employed in this study and have confirmed their specificity to their target. We have noted that the sensitivity of the anti-human IgG1 antibody used can benefit from a higher concentration; however, it would come at a cost of compromising its specificity as the antibody shows cross-reactivity to other IgG subtypes at slightly increased concentrations, therefore, presenting a less favorable sensitivity-to-specificity profile than the other secondary antibodies.…”
Section: Discussionsupporting
confidence: 63%
“…Our observation was corroborated by repeating the measurements using the same IgG4-specific secondary antibody as well as by using the same clone from an alternative source (including differences in concentrations and storage buffers), which makes us confident that the results presented are valid. Moreover, we presented one of the most comprehensive cross-validations to date of all secondary antibodies -widely used in research on SARS-CoV-2 (Crowley et al, 2021;Fraley et al, 2021;Kim et al, 2021;Lee et al, 2021;Newell et al, 2021;Phelan et al, 2021;Pullen et al, 2021;Yates et al, 2021) and in other fields (Minassian et al, 2021;Sanchez Vargas et al, 2021;Tschismarov et al, 2021;Jennewein et al, 2022;Toney et al, 2022) -employed in this study and have confirmed their specificity to their target. We have noted that the sensitivity of the anti-human IgG1 antibody used can benefit from a higher concentration; however, it would come at a cost of compromising its specificity as the antibody shows cross-reactivity to other IgG subtypes at slightly increased concentrations, therefore, presenting a less favorable sensitivity-to-specificity profile than the other secondary antibodies.…”
Section: Discussionsupporting
confidence: 63%